Security, Archivists, and Digital Collections. Issue 1 (3rd April 2018) - Donaldson, Devan Ray; Bell, Laura
Abstract: This article presents results from an exploratory survey of 15 archivists, librarians, directors, and technicians regarding the security of digital collections. Participants defined security in terms of integrity, confidentiality, availability, detecting malicious actors, protection from physical damage, and protection from viruses. Findings suggest that while some participants reported encountering security threats related to confidentiality and availability, others reported that they either had not encountered any security threats or did not know if they had. This paper concludes by considering archivists' knowledge of securing digital collections and their collaboration with IT staff. Future directions for research are discussed.